Universal Service for the Twenty-First Century - Raiche, Holly (Journal of Telecommunications and the Digital Economy, 2024)
The Australian Government is asking Australians for their views on the existing telecommunications universal service obligation. Fifty years ago, that obligation was on Telecom (now Telstra) to provide payphones and a voice service that would best meet the social, industrial and commercial needs of all Australians who reasonably require those services, so far as it is reasonably practicable to do so. The obligation is still the same: the provision of payphones and voice telephony. If the universal service obligation is to have any continuing relevance in the Australian communications framework, however, it must reflect the social, industrial and commercial needs of Australians in 2024 and beyond. Research shows that Australians are using broadband services for a wide range of services in their lives: access to government services, health, finances, education, entertainment, and social and family connections. And for the large majority of Australians, that communication is by mobile telephony. A new definition of the service for all Australians must be upgraded to reflect how Australians now communicate. And it must be continually reviewed and upgraded as necessary to meet the changing communications needs of all Australians.